Pengembangan Buku Cerita Digital Bukber (Buku Berbakti) pada Pembelajaran PAI di Sekolah Dasar - Fariza, Aghisni Nur; Resvia, Dea Sifa; Laelasari, Laelasari; Ariella, Rinrin Alva; Aeni, Ani Nur (Attractive : Innovative Education Journal, 2024)
This research was motivated by the unavailability of interactive learning media at Situraja I State Elementary School. This is a challenge for teachers to increase students' enthusiasm and interest in learning, especially in material devoted to parents and teachers. The research developed a product in the form of interactive learning media, the BUKBER Digital Story Book (Bakti Book). This research uses the Design and Development (D&D) model as a tool to convey material about filial piety to parents and teachers in PAI learning for grade 4 elementary schools. The data processing technique that researchers use is qualitative. Data was obtained based on observations during testing. From the results of data analysis on the development of BUKBER (Buku Berbakti), it shows the feasibility in the final results of the product feasibility validation questionnaire evaluation by the validator. Next, researchers conducted product trials on 26 students which produced data that the BUKBER Digital Story Book (Bakti Bakti) learning media was effectively used in PAI learning in class 4 of Situraja 1 State Elementary School. Keywords: Digital books, Devotion, Islamic Religious Education